Bentuk Perlindungan Hukum Penyelesaian Sengketa Pinjaman Online di Indonesia (Suatu Pendekatan Norma Hukum) - Rosmidah, Rosmidah; Yahya, Taufik; Wulansari, Ditya Putri (Universitas Batanghari Jambi, 2024)
The research aims to explore and analyze legal protection for parties in online loan transaction disputes and alternative dispute resolution through online loan application service networks. The type of research is normative legal research (normative research) using a statutory approach, a conceptual approach, analysis of legal materials is carried out by interpreting and assessing related laws and regulations and selecting relevant legal materials. The research results show that legal protection for parties in transaction disputes through the online loan application service network must be based on an agreement based on mutual agreement with the legal online loan provider and a dispute resolution institution must be determined in the initial agreement, carrying out legal enforcement for unlawful acts committed by the provider. and provide, in principle, this protection to protect the rights of debtors as consumers, resolving disputes in online loan transactions for technology-based loan actors because borrowers still do not know in detail the dispute resolution mechanism, Financial Services Authority Regulation Number 77/POJK. 01/2016 Article 29 letter e only regulates the principle of dispute resolution which is carried out simply, quickly and at low cost, the parties can freely choose a dispute resolution institution that has been recommended by the Financial Services Authority.